2014
DOI: 10.3389/fnana.2014.00103
|View full text |Cite
|
Sign up to set email alerts
|

Neocortical calretinin neurons in primates: increase in proportion and microcircuitry structure

Abstract: In this article we first point at the expansion of associative cortical areas in primates, as well as at the intrinsic changes in the structure of the cortical column. There is a huge increase in proportion of glutamatergic cortical projecting neurons located in the upper cortical layers (II/III). Inside this group, a novel class of associative neurons becomes recognized for its growing necessity in both inter-areal and intra-areal columnar integration. Equally important to the changes in glutamatergic populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
60
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 89 publications
15
60
1
Order By: Relevance
“…These cells often exhibited bipolar or bitufted morphology and coexpressed CR and VIP (Fig. 4E-J), consistent with CGE/LGE origins (Xu et al 2004;Fogarty et al 2007;Miyoshi et al 2010;DeFelipe et al 2013;Ma et al 2013;Dzaja et al 2014;Hladnik et al 2014). …”
Section: Secretagogin Expression In Human Neocortex Is Developmentallmentioning
confidence: 74%
See 2 more Smart Citations
“…These cells often exhibited bipolar or bitufted morphology and coexpressed CR and VIP (Fig. 4E-J), consistent with CGE/LGE origins (Xu et al 2004;Fogarty et al 2007;Miyoshi et al 2010;DeFelipe et al 2013;Ma et al 2013;Dzaja et al 2014;Hladnik et al 2014). …”
Section: Secretagogin Expression In Human Neocortex Is Developmentallmentioning
confidence: 74%
“…The increase in the proportion of GABAergic neurons in primate neocortex is thought to primarily reflect an increase in the vasoactive intestinal polypeptide (VIP)/calretinin (CR)-expressing subtype (Hansen et al 2013;Dzaja et al 2014;Hladnik et al 2014;Barinka et al 2015), which arises in the caudal and lateral ganglionic eminences (CGE/LGE) and preferentially occupies superficial cortical layers (Xu et al 2004;Fogarty et al 2007;Miyoshi et al 2010). In humans, half or more of neocortical GABAergic neurons may derive from the CGE (Hansen et al 2013), whereas in mice this number is closer to~30% (Miyoshi et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A later study found that a subpopulation of Emx1 -lineage cells originating in the pallium migrates to the developing striatum during early prenatal development [41] and differentiates primarily into DARPP-32-positive medium-sized spiny neurons but also a small number of CR-positive (but no other) striatal interneurons [42]. The pallium has been proposed as the main source of CR+ interneurons in the primate neocortex–and the explanation for the specific expansion of this interneuron subtype in primates [43,44]. It is not yet clear whether any or all adult-born striatal interneurons derive from the Emx-1 lineage in the normal rodent, but these young neurons would represent a small proportion of the interneurons or Emx-1-derived neurons in the rodent striatum and could easily be overlooked.…”
Section: The Origin Of New Striatal Neuronsmentioning
confidence: 99%
“…33 Even though this is a relatively small fraction of the inhibitory neurons, their unique connectivity and placement in the circuitry affords them significant control over inhibitory regulation as a whole. 34 They have been described as being at the top of the intemeuron hierarchy due to the fact that they preferentially regulate the activity of other interneuron populations and specifically target dendritic inhibitory intemeurons to synchronize their activity. 35 • 36 This synchronization of dendritic inhibitory cells is a crucial process to provide effective inhibitory control of excitatory pyramidal cells.…”
Section: Response Of Interneurons To Tbimentioning
confidence: 99%